THE IMPORTANCE OF ORGANISATIONAL CULTURE IN IT COMPANIES - MARIA MAGDALENA CRIVEANU; CONSTANTIN RENATO IVANESCU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2019)
Ten years after the economic crisis that affected almost all economic sectors in our country, Romania is facing a new crisis, i.e. the labour crisis, especially seen in the private environment, where more and more companies choose to shut down for these reasons. According to official data, Romania is the second country in the world in terms of migration, after Syria. Such a negative factor impacts the economy, as the latter can only develop with the help of labour, which, in this case, has become a very scarce and expensive resource. In this context, employers are affected by the fact that employees easily leave their jobs and cannot be replaced. This is why they are constantly searching for new ways to prevent such issues and try to find solutions to retain labour force. One of the most important issues to be considered refers to the notion of organisational culture, as this might be a key component differentiating between companies.